2017
DOI: 10.3847/1538-3881/153/3/111
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy And Mass Assembly (GAMA): Gas Fueling of Spiral Galaxies in the Local Universe. I. The Effect of the Group Environment on Star Formation in Spiral Galaxies

Abstract: We quantify the effect of the galaxy group environment (for group masses of 10 12.5 -1014.0 M e ) on the current star formation rate (SFR) of a pure, morphologically selected sample of disk-dominated (i.e., late-type spiral) galaxies with redshift 0.13. The sample embraces a full representation of quiescent and star-forming disks with stellar mass M * 10 9.5 M e . We focus on the effects on SFR of interactions between grouped galaxies and the putative intrahalo medium (IHM) of their host group dark matter ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 214 publications
(475 reference statements)
2
27
0
Order By: Relevance
“…16 shows the "main sequence" relation between integrated quantities SFR and M * for a flux-limited subset (complete to 19.4 mag in the SDSS r-band) of 5202 disc-dominated GAMA galaxies located within redshift 0.13, and which are not classified as belonging to a galaxy group (see Table 1 and Sect. 4.3 of Grootes et al 2017). We refer to this subsample, plotted as dots on the figure, as the "field" reference sample of disc-dominated galaxies.…”
Section: Comparison Of M33 With the Population Of Disk-dominated Galamentioning
confidence: 99%
See 2 more Smart Citations
“…16 shows the "main sequence" relation between integrated quantities SFR and M * for a flux-limited subset (complete to 19.4 mag in the SDSS r-band) of 5202 disc-dominated GAMA galaxies located within redshift 0.13, and which are not classified as belonging to a galaxy group (see Table 1 and Sect. 4.3 of Grootes et al 2017). We refer to this subsample, plotted as dots on the figure, as the "field" reference sample of disc-dominated galaxies.…”
Section: Comparison Of M33 With the Population Of Disk-dominated Galamentioning
confidence: 99%
“…SFR versus stellar mass for a field reference sample of local universe disc-dominated galaxies (black points) and the global emission from M33 (red rhomboid). The field reference sample is comprised of of 5202 morphologically selected, diskdominated galaxies drawn from the GAMA survey by Grootes et al (2017), which are not members of groups of galaxies. The vertical and horizontal apexes of the rhomboid containing the M33 point are placed at the 1-sigma bounds in SFR and M * , respectively.…”
Section: Comparison Of M33 With the Population Of Disk-dominated Galamentioning
confidence: 99%
See 1 more Smart Citation
“…This could be interpreted as the result of their environment acting to prematurely reduce the cold gas supply to an increasing subset, presumably through galaxy-galaxy, or galaxy-intra group medium interactions (strangulation, ram pressure stripping etc. -see Grootes et al 2017 for an extensive discussion). The velocity dispersions (from Robotham et al 2011) of the less rich environments vary from typically ∼ 200 to ∼ 350 kms −1 for systems with multiplicities up to 20 galaxies, but can be ∼ 500 kms −1 or more for the richest subset in Table 1.…”
Section: A Simple Modelmentioning
confidence: 99%
“…Using a similar method, Oman & Hudson (2016) derive an infall time of ∼ 4 Gyr and quenching timescales between 4 − 6 Gyr for galaxies in the mass range of the gz2-group-q sample. However, studies such as Peng et al (2010); Wetzel et al (2013); Hahn et al (2016); Crossett et al (2017) and Grootes et al (2017) have found much shorter quenching timescales of ∼ < 1 Gyr for satellite galaxies.…”
Section: The Role Of the Environment In Quenchingmentioning
confidence: 99%